2005
DOI: 10.1111/j.1460-9568.2005.04452.x
|View full text |Cite
|
Sign up to set email alerts
|

Ephrin‐A4 inhibits sensory neurite outgrowth and is regulated by neonatal skin wounding

Abstract: The mechanisms for directing and organising sensory axons within developing skin remain largely unknown. The present study provides the first evidence that signalling occurs between A-ephrins and Eph-A receptors during the development of rat cutaneous sensory innervation both during normal development and following skin injury. Specifically, our data indicate that ephrin-A4 mRNA and protein are expressed in the epidermis during late embryogenesis and the early postnatal period (E16-P3), and expression is signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 56 publications
2
27
0
Order By: Relevance
“…Accordingly, the EphA2-Fc treatment of CLL cells diminishes the proportion of cell conjugates established between them and HUVECs in an EFNA4 expression-dependent manner. EFNA4 reverse signaling has been reported to act through repulsive signals in other systems like inhibiting sensory neurite outgrowth within the developing mouse skin, 30 further suggesting that this molecule can lead to repulsive signals during cell-cell contacts in the TEM process.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the EphA2-Fc treatment of CLL cells diminishes the proportion of cell conjugates established between them and HUVECs in an EFNA4 expression-dependent manner. EFNA4 reverse signaling has been reported to act through repulsive signals in other systems like inhibiting sensory neurite outgrowth within the developing mouse skin, 30 further suggesting that this molecule can lead to repulsive signals during cell-cell contacts in the TEM process.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we do not know the actual levels of NgR2 receptor proteins on DRG axons from different subclasses, so it is unclear whether this phenotype results from a reduced NgR2 surface expression or from a lack of potential coreceptors required for NgR2-signaling. The NgR receptor complex contains both, the NgR and either the neurotrophin receptor p75 NTR or the orphan receptor TNF family member TROY (Mironova and Giger, 2013), but the functional signaling partner for NgR2 in sensory DRG neurons is currently unknown. A recent study suggests that NgR2 associates with TROY to limit synapse formation of hippocampal neurons in vitro (Wills et al, 2012).…”
Section: Ngr2 Is Required To Mediate Sensitivity To Versicanmentioning
confidence: 99%
“…The binding of ligands (ie, Ephrin-A1, Ephrin-A3, Ephrin-A4, Ephrin-A5) is the premise for the inhibitory effect of EphA4. Moreover, it was found that Ephrin-A4 inhibited neurite growth in the peripheral nervous system [5] . Inhibiting and reversing the activation of astrocytes appears to be rational and practical.…”
Section: Introductionmentioning
confidence: 99%